From "Global Britain" to Realpolitik - the updated Integrated Review: How the United Kingdom wants to position itself as a reliable partner in a competitive global order - Nicolai von Ondarza; Dominik Rehbaum (Stiftung Wissenschaft und Politik (SWP), 2023)
Almost two years after the publication of the "Integrated Review", the British government has updated its security strategy. This "refresh" is primarily intended to adapt to the rapidly advancing development towards a contested and fragmented global order. Without indicating a radical shift, the strategy specifies the British response to China and Russia and places a special focus on the role of partners as well as on national resilience. Following the leadership change in the British government to Rishi Sunak, the paper sets out a more pragmatic approach for future cooperation with the European Union (EU). In order to advance the implementation of the Integrated Review and strengthen Euro-Atlantic relations, Germany and the EU should seize the momentum and deepen their cooperation with London.
Keywords: 320; United Kingdom; Integrated Review (IR21); NATO; Brexit; United States; European Union (EU); France; Germany; China; Russia; Indo-Pacific; Euro-Atlantic relations; war Ukraine; Covid 19 pandemic; Rishi Sunak